If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + y = -32 Solving 12 + y = -32 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + y = -32 + -12 Combine like terms: 12 + -12 = 0 0 + y = -32 + -12 y = -32 + -12 Combine like terms: -32 + -12 = -44 y = -44 Simplifying y = -44
| 10x-13=-x+9 | | 3(2x-5)+6x-2= | | x^3-6x^2-48=0 | | -6(5x+5)=-180 | | y+-31=6 | | y+-43=-41 | | x+-18=-32 | | 16+3-1*3=10 | | -3(4b+1)=-63 | | 12.00+-2.00x=10.00 | | 3p^2-5p-18=0 | | 35x^2=-x+6 | | 6v+11=3v+8 | | x+-29=1 | | 37-2(c+3)=4(c+5)+c | | 57*3=2x | | 18x+7(5x-9)+5(2x+7)+9=2x+5 | | -x-5=2x-5 | | 11+x=-19 | | 6(5p-2)=138 | | x+-44=-81 | | 98(-3)+98(3)=y | | -2w+8=-4w | | x+9x+4=0 | | 2+4lnx=12 | | 4x-2+5x+4=2x-3x+3-4 | | 5.2k=3.7+12.9 | | n+1=n | | -13+-5x=-43 | | -46+x=-72 | | 9x^2+22x-49-13x^2-8x+15= | | 12x+4=9+4x |